If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -5)(4x + 8) = 0 Reorder the terms: (-5 + 6x)(4x + 8) = 0 Reorder the terms: (-5 + 6x)(8 + 4x) = 0 Multiply (-5 + 6x) * (8 + 4x) (-5(8 + 4x) + 6x * (8 + 4x)) = 0 ((8 * -5 + 4x * -5) + 6x * (8 + 4x)) = 0 ((-40 + -20x) + 6x * (8 + 4x)) = 0 (-40 + -20x + (8 * 6x + 4x * 6x)) = 0 (-40 + -20x + (48x + 24x2)) = 0 Combine like terms: -20x + 48x = 28x (-40 + 28x + 24x2) = 0 Solving -40 + 28x + 24x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(-10 + 7x + 6x2) = 0 Factor a trinomial. 4((-2 + -1x)(5 + -6x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(5 + -6x)' equal to zero and attempt to solve: Simplifying 5 + -6x = 0 Solving 5 + -6x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -6x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -6x = 0 + -5 -6x = 0 + -5 Combine like terms: 0 + -5 = -5 -6x = -5 Divide each side by '-6'. x = 0.8333333333 Simplifying x = 0.8333333333Solution
x = {-2, 0.8333333333}
| 2.5(2x+4)=30 | | 5(3x-8)-2=-33-15x | | 2b^2=-6 | | 9x^2+16=25 | | x+18x=3 | | 5(3x-8)-2=-33-15v | | 18x^3-4x^2+10x= | | 55-55= | | 6.5x+x=74 | | -6(2+a)=48 | | 6r-60=12 | | 5a^2=-13a-6 | | 7x^2-3=67 | | 6+c=22 | | c^4-9c^2+20=0 | | 5x+2=6x+-4 | | 0=9x-y+5 | | 8x^2+5x+7=0 | | Y=4x^2+2x+1 | | v^2+7v+30=0 | | z-(-40)=33 | | x+20=1/3(234) | | Y=-0.2(40)+50 | | 4x-27+(x+39)=180 | | 4X^2+2x+1=y | | x-16=2/3x | | 7x-(3x+10)=-x+15 | | 5x^2+33x=-18 | | p=5-4p | | 7x-3-2x=24-4x | | 6-(-5-11)= | | N^2+10=6 |